IMPLEMENTATION OF KAMPUS MENGAJAR 3 AS AN EFFORT TO IMPROVE LITERATURE AND NUMERATION CAPABILITIES OF STUDENTS - Krisna Syarif Hidayatullah; Dida Rahmadanik (Citra Dharma Cindekia, 2022)
Kampus Mengajar is one of the activities of Merdeka Belajar Kampus Mengajar (MBKM) which is engaged in teaching activities. Kampus Mengajar has three main objectives, namely improving literacy and numeracy, adapting technology and assisting administration in schools. This research focuses on efforts to improve literacy and numeracy in elementary schools that have 3T criteria (Lagged, Outermost, and Frontier). The research method used is a descriptive qualitative approach. The target public elementary school is SDN Darungan 02 as the research subject. The object of the research is an effort to improve literacy and numeracy at SDN Darungan 02, Tanggul, Jember Regency. Data collection using observation and documentation techniques. From the results of the study, it can be concluded that the process of increasing literacy and numeracy by using the consistency learning method in practicing reading, discussing, counting and showing learning videos has a positive impact on students in improving literacy and numeracy skills. The Kampus Mengajar Program also encourages students to evaluate and map literacy and numeracy learning outcomes by carrying out a pretest and posttest for the Minimum Competency Assessment (AKM), especially for grade 5. The AKM assessment also aims to make students accustomed to taking tests using computers/laptops.